Severe Acute Respiratory Infections (SARI) surveillance in over-65-years-old patients: the experience of a University hospital (seasons 2017-2018 and 2018-2019) - Bertamino, E.; Zerbetto, A.; Capalbo, C.; Alfonsi, V.; Petrucca, A.; Santino, I.; Bonfini, R.; Aromatario, M.; Pomes, L. M.; Mancini, R.; Ferracuti, S.; Rizzo, C.; et al. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Background. Influenza is a relevant public health problem, also due to the risk of complications. The most effective measure to prevent influenza is vaccination; therefore, at present, there is consensus among European countries, regarding the need for routine seasonal influenza vaccination of elderly and individuals at increased risk of severe influenza. At the same time, influenza surveillance is necessary to understand the viruses circulating and effectiveness of vaccination strategies. The present study reports the results of two seasons influenza surveillance (2017/2018 and 2018/2019) conduced in an University Hospital in Rome among hospitalized patients aged ≥65 years. Study design. A prospective cohort study. Methods. The study consisted of systematic daily screening of all admissions among patients aged ≥65 years meeting a syndromic SARI case definition during two consecutive influenza seasons: 2017/2018 and 2018/2019. Characteristics of patients and their risk factors were collected by a standardized questionnaire and nose-pharyngeal swabs were performed to each patient. Influenza vaccine effectiveness (IVE), rates of vaccinated subjects and case fatality rate were also evaluated. Results. Influenza was laboratory confirmed in 11 (9.9%) of the 111 and 11 (9.6%) of the 115 enrolled patients in seasons 2017/18 and 2018/19, respectively. Adjusted IVE against all influenza type, calculated for each season, was 88.5% (95% CI: 38.9 to 97.8) and 61.7% (95% CI: -59.9 to 90.9) for 2017/2018 and 2018/2019 seasons, respectively. Our analysis shows a Case Fatality Rate of 2.7% and 4.3% for the 2017/18 and 2018/19 seasons, respectively. Conclusions. The surveillance of SARI conduced in one hospital in Rome confirmed that influenza is an important cause of hospital admissions. Routine monitoring of infectious diseases and related aetiology associated with SARI, also at the local-level, is useful for targeting the right preventive measures.